Treatment failure with penicillin in early syphilis. Issue 1 (February 1979) - Giles, A J; Lawrence, A G
Abstract : A patient with primary syphilis had a recurrence of his penile chancre after generally acceptable penicillin treatment. Retreatment with a similar but extended penicillin regimen was successful. This is the first report of such a treatment failure.